Strength Versus Sensitivity: The Impact of Attorney Gender on Juror Perceptions and Trial Outcomes in a Rape Case - Levi, Mary M. (Violence against women, 2022)
We examined the impact of attorney gender on perceptions of a criminal rape trial. Community members (N = 208) read a trial summary describing a rape scenario in which the gender of the prosecuting and defense attorney were manipulated. The results revealed indirect effects of prosecuting and defense attorney gender on verdict through perceptions of characteristics related to attorney competency. Qualitative analyses further showed that the terms “strength” and “powerful” were central to juror perceptions of male attorneys, whereas the terms “sensitive” and “sympathy” were central when the attorneys were female.